Surgical Outcomes of Porcine Acellular Dermis Graft in Anophthalmic Socket: Comparison with Oral Mucosa Graft - Teo, Livia; Woo, Young Jun; Kim, Dong Kyu; Kim, Chang Yeom; Yoon, Jin Sook (Korean journal of ophthalmology, 2017)
We describe our experience with the Permacol graft in anophthalmic socket reconstruction, and compare it to the autologous buccal mucosal graft, emphasizing the postoperative vascularization and contraction of each graft. This was a retrospective comparative study. We measured the time necessary for the graft surface to be completely vascularized, as well as the fornix depth of the conjunctival sac in anophthalmic patients. Ten patients underwent Permacol graft reconstruction, with 44 undergoing buccal mucosal graft reconstruction. Seven eyelids (70%) in the Permacol group had a good outcome, with improvement in lower eyelid position and prosthesis retention. Nine out of 10 eyelids (90%) in this group showed complete vascularization of the graft at 2.6 ± 1.9 months postoperatively, while the grafted buccal mucosa was fully vascularized at 1.1 ± 0.3 months postoperatively ( < 0.01). Postoperative fornix depth in the Permacol group was 9.1 ± 2.2 mm, compared to 14.9 ± 4.5 mm in the buccal mucosal graft group ( < 0.01). Mean increases in fornix depth were 33.1% and 67.9% of the mean vertical length of the implanted graft. The Permacol graft can be useful as spacer graft material in anophthalmic socket patients. It takes longer to vascularize, and undergoes greater graft shrinkage with time, compared to the buccal mucosal graft.